The educational role of informal training in creating an entrepreneurial model of new business - Fakher, Ghadir (2021)
Entrepreneurship development is important for any business. The purpose of this study is to present an entrepreneurial model for start-ups focused on the impact of innovation and non-formal education. The present research model examines the role of informal training on business performance and customer expectation estimation. The derived theoretical model was tested on 100 startup business data in Iran. The PLS-SEM analysis showed that non-formal education directly affected the performance of businesses. Findings showed that human capital is one of the determinants of non-formal education. The mediating effect of informal training and customer expectation estimation on the relationship between HR quality and business performance was quite evident.